2022
DOI: 10.3389/fphar.2022.872912
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin, a Phytochemical From Chili Pepper, Alleviates the Ultraviolet Irradiation-Induced Decline of Collagen in Dermal Fibroblast via Blocking the Generation of Reactive Oxygen Species

Abstract: Capsaicin, a major ingredient in chili pepper, has broad pharmaceutical applications, including relieving pain, anti-inflammation, and treating psoriasis. In dermatological biology, capsaicin has been shown to prevent the ultraviolet (UV)-induced melanogenesis via TRPV1 receptor. To strengthen the roles of capsaicin in skin function, the damaged skin, triggered by exposure to UV, was reversed by capsaicin in both in vitro and in vivo models. In cultured dermal fibroblasts, the exposure to UV induced a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…monocytes and macrophages, express a7 nAChR in controlling skin homeostasis [23]. During UV-induced photoaging or photo-dermatoses, the application of a7 nAChR agonists has been reported to reduce the production of inflammatory cytokines, as well as the ROS-mediated collagen degradation in keratinocytes and skin fibroblasts [16,24,25]. The current results supported that a7 nAChR can regulate skin pigmentation, in which the activation of a7 nAChR potentiates phagocytic activity, or melanosome uptake, of keratinocytes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…monocytes and macrophages, express a7 nAChR in controlling skin homeostasis [23]. During UV-induced photoaging or photo-dermatoses, the application of a7 nAChR agonists has been reported to reduce the production of inflammatory cytokines, as well as the ROS-mediated collagen degradation in keratinocytes and skin fibroblasts [16,24,25]. The current results supported that a7 nAChR can regulate skin pigmentation, in which the activation of a7 nAChR potentiates phagocytic activity, or melanosome uptake, of keratinocytes.…”
Section: Discussionsupporting
confidence: 75%
“…The exposure to UVB can cause the formation of reactive oxygen species (ROS) in keratinocytes [15,16]. The relevance of ROS formation and UVB-induced phagocytosis was examined.…”
Section: Uvb-induced Ros Formation Has No Role In Phagocytosismentioning
confidence: 99%
“…A study has revealed that capsaicin boosted collagen synthesis in cultured dermal fibroblasts via extracellular signal-regulated kinases (Erk)/c-Jun-mediated MMP signaling. Moreover, the application of low-dose capsaicin on the shaved mouse dorsal skins alleviated the UV-induced reduction of collagen ( Wu et al, 2022 ). In addition, baicalein suppressed MMP-1 expression by activating the TRPV1-Ca 2+ -ERK pathway in UVB-irradiated human dermal fibroblasts ( Huang et al, 2019 ).…”
Section: The Role Of Trpv1 In Skin Agingmentioning
confidence: 99%
“…Understanding capsaicin research from global perspectives over an extended time is crucial. Although several studies have been published on capsaicin applications, bioactivities, and many other capsaicin-related topics (33)(34)(35), none of these studies explored the scientometric approach to critically assess its progress and current direction in scientific research. Bibliometrics is a valuable tool for evaluating research trends within a subject area, thus providing insight into extensively researched themes and identifying research needs to inform action (36).…”
Section: Introductionmentioning
confidence: 99%